2014
DOI: 10.1016/j.amepre.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Use of Psychology and Behavioral Economics to Promote Healthy Eating

Abstract: Understanding the psychology of how people make decisions can shed light on important factors contributing to the cause and maintenance of public health problems like obesity. This knowledge can and should inform the design of government and private-sector public health interventions. Several insights from psychology and behavioral economics that help explain why people are particularly vulnerable to the current food environment are discussed. These insights fall into the following categories: the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 59 publications
1
62
0
Order By: Relevance
“…For example, if children were likely to order French fries and additional a la carte sides, interventions aimed just at reducing French fry intake would miss other important meal characteristics. LCA can also detect ordering patterns that represent a small, but meaningful subgroup of the study population, which can help avoid potential unintended consequences of interventions by enabling interventionists to tailor programs to reach all members of the population .…”
Section: Introductionmentioning
confidence: 99%
“…For example, if children were likely to order French fries and additional a la carte sides, interventions aimed just at reducing French fry intake would miss other important meal characteristics. LCA can also detect ordering patterns that represent a small, but meaningful subgroup of the study population, which can help avoid potential unintended consequences of interventions by enabling interventionists to tailor programs to reach all members of the population .…”
Section: Introductionmentioning
confidence: 99%
“…The framing of choices has been found to have a paramount impact on decision making, particularly when making the intertemporal trade‐off between “should” and “want” behaviors . Highlighting the positive attributes of the “should behaviors” (eg, physical activity) rather than the negative ones is an important factor that can change the current status quo . Thus the public health message delivered to patients encouraging them to engage in physical activity should be positive and simple .…”
Section: Status Quo Biasmentioning
confidence: 99%
“…102 For example, First Lady Michelle Obama's initiative to combat childhood obesity, "Let's Move!," was a good example of a positive and simple message. 102,103 In addition, physical activity should be framed as a fun activity (eg, "go out there, choose an activity you like, such as dancing or soccer, and have fun") rather than an obligatory activity (eg, "you need to meet guidelines, because it's important for improving your health"). 26 In addition, a recent study by Grinstein and Kronrod underscored the importance of not only what is said in the health message but also how the message in conveyed.…”
Section: Framing and Anchoringmentioning
confidence: 99%
“…(9) In particular, point-of-purchase strategies used in supermarkets, corner stores, and worksite cafeterias such as choice architecture (10,11) and traffic-light labels (12) have been shown to be effective for promoting healthier food choices. Previous work in Latino food stores has shown that in-store environmental factors such as placement and promotion strategies are associated with increased fruit and vegetable purchases among Latino shoppers.…”
Section: Introductionmentioning
confidence: 99%